A brief history of the Department of Animal Sciences and Industry at Kansas State University - Miles McKee (Kansas Agricultural Experiment Station Research Reports, 2005)
The Department of Animal Sciences and Industry at Kansas State University celebrates its 100th anniversary this year. This review outlines some of the key historical moments in its development.
Keywords: Cattlemen& #x27; s Day; 2005; Kansas Agricultural Experiment Station contribution; no. 05-144-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 943; Beef; History